2015
DOI: 10.1371/journal.pgen.1005140
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal Remodeling of Functional Membrane Microdomains Organizes the Signaling Networks of a Bacterium

Abstract: Lipid rafts are membrane microdomains specialized in the regulation of numerous cellular processes related to membrane organization, as diverse as signal transduction, protein sorting, membrane trafficking or pathogen invasion. It has been proposed that this functional diversity would require a heterogeneous population of raft domains with varying compositions. However, a mechanism for such diversification is not known. We recently discovered that bacterial membranes organize their signal transduction pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 99 publications
2
60
0
Order By: Relevance
“…Although we were capable of detecting a high MW complex containing various PBPs (notably PBP1, 2a, 2b, 3 and 4), the complex was not dependent on the presence of flotillins. We also note that PBP1 was present in the complex, as well as present in a large smear in the first dimension native gel, which would explain why PBP1 was detected by mass spectrometry analysis of a native PAGE band containing FloA 29 . PBP5, on the other hand, was not part of the high MW complex, which fits with its role in processing of the terminal D-Ala from stem-peptides that have not been cross-linked, which it exercises over the entire surface of the cell 32 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although we were capable of detecting a high MW complex containing various PBPs (notably PBP1, 2a, 2b, 3 and 4), the complex was not dependent on the presence of flotillins. We also note that PBP1 was present in the complex, as well as present in a large smear in the first dimension native gel, which would explain why PBP1 was detected by mass spectrometry analysis of a native PAGE band containing FloA 29 . PBP5, on the other hand, was not part of the high MW complex, which fits with its role in processing of the terminal D-Ala from stem-peptides that have not been cross-linked, which it exercises over the entire surface of the cell 32 .…”
Section: Discussionmentioning
confidence: 78%
“…Cell morphology effects are linked to cell wall synthesis, and analysis of the protein content of Bacillus subtilis DRMs identified several PBPs, MreC and other proteins involved in cell wall metabolism as well as the two flotillins, FloA and FloT 21,24,26 . FloA is constitutively expressed, whereas FloT is expressed primarily during stationary growth, cell wall stress and sporulation 27-29 . Super resolution microscopy showed that the flotillins and other proteins found in DRMs do not colocalize and have different dynamics 30 , so it is unlikely that FMMs are regions in the membrane that offer a favourable environment in which these membrane proteins are continuously present and active.…”
Section: Introductionmentioning
confidence: 99%
“…The localization of PII‐PipX complexes into peripherally located foci appears reminiscent of the recently described membrane microdomains that are involved in organizing signalling networks in B. subtilis (Schneider et al ., ). In the light of the results obtained here, we propose that PII‐PipX complexes are involved in a signalling pathway that transmits signals of energy abundance to essential cell processes, facilitating adaptation to the new environmental conditions.…”
Section: Resultsmentioning
confidence: 97%
“…The organization of FMMs in bacteria involves the biosynthesis and aggregation of isoprenoid-related membrane saccharolipids 47,48 and their colocalization with flotillin-homolog proteins 47,49 . Bacterial flotillins, like their eukaryotic counterparts, are microdomain-associated scaffold proteins responsible for providing stability to FMMs and for recruiting protein cargo to the latter 27,32,50 . Thus, FMMs act as platforms for promoting the efficient oligomerization of protein complexes, and their organization influences cellular processes.…”
Section: Introductionmentioning
confidence: 99%